Comparison of Clinical Characteristics for Distinguishing COVID-19 From Influenza During the Early Stages in Guangdong, China - Li, Yongzhi; He, Huan; Gao, Yuhan; Ou, Zejin; He, Wenqiao; Chen, Caiyun; Fu, Jiaqi; Xiong, Husheng; Chen, Qing (Frontiers in Medicine, 2021)
Background: To explore the differences in clinical manifestations and infection marker determination for early diagnosis of COVID-19 and influenza (A and B). Methods: A hospital-based retrospective cohort study was designed. COVID-19 patients and influenza inpatients at a sentinel surveillance hospital were recruited. Demographic data, medical history, laboratory findings, and radiographic characteristics were summarized and compared between the two groups. The chi-square test or Fisher’s exact test was used for categorical variables, and Kruskal–Wallis H test was used for continuous variables in each group. Receiver operating characteristic curve (ROC) was used to differentiate the intergroup characteristics. Cox proportional hazards model was used to analyze the predisposing factors. Results: Twenty-three COVID-19 patients and 74 influenza patients were included in this study. Patients with influenza exhibited more symptoms of cough and sputum production than COVID-19 (P<0.05). Computed tomography showed that consolidation and pleural effusion were more common in influenza than COVID-19 (P<0.05). Subgroup analysis showed that influenza patients had high values of infection and coagulation function markers, but low values of blood routine and biochemical test markers than COVID-19 patients (mild or moderate groups) (P<0.05). In COVID-19 patients, the ROC analysis showed positive predictions of albumin and hematocrit, but negative predictions of C-reactive protein (CRP), procalcitonin (PCT), lactate dehydrogenase (LDH), hydroxybutyrate dehydrogenase (HBDH), and erythrocyte sedimentation rate. Multivariate analysis revealed that influenza might associated with risk of elevated CRP, PCT, and LDH, while COVID-19 might associated with high HBDH. Conclusion: Patients with influenza had more obvious clinical symptoms but less common consolidation lesions and pleural effusion than those with COVID-19. These findings suggested that influenza likely presents with stronger inflammatory reactions than COVID-19, which provides some insights into the pathogenesis of these two contagious respiratory illnesses.